2017
DOI: 10.1039/c6ra26249j
|View full text |Cite
|
Sign up to set email alerts
|

Morphology evolution of Ag/Au nanocomposites via temperature-controlled galvanic exchange to enhance catalytic activity

Abstract: Morphology-controlled Ag/Au nanocomposites have been fabricated facilely via a modified galvanic replacement reaction using Ag nanocubes as sacrificial templates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Over the last few years, the poising tolerance and the activities of the Pt-based catalyst were improved by introducing various shapes of nanostructures including nanowires 15,16 , nanoparticles 17 , mesoporous 18 , nanospheres 19,20 , and nanotubes 21,22 . Hollow metallic nanoarchitectures are an interesting class of materials due to their unique physical and chemical properties 23 . Hollow nanostructures are considered an extraordinary morphology due to their ‘nanoreactor confinement effect’.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, the poising tolerance and the activities of the Pt-based catalyst were improved by introducing various shapes of nanostructures including nanowires 15,16 , nanoparticles 17 , mesoporous 18 , nanospheres 19,20 , and nanotubes 21,22 . Hollow metallic nanoarchitectures are an interesting class of materials due to their unique physical and chemical properties 23 . Hollow nanostructures are considered an extraordinary morphology due to their ‘nanoreactor confinement effect’.…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic nanoparticles (Ag–Au and Au–Cu) with porous nanostructure and larger cavities have shown better catalytic performance than those with solid morphology in the literature reports. 48–50 Based on the morphological characterization of treated Au–Ag@HNT, we noticed that porous Au–Ag@HNT became solid Au–Ag@HNT after heating at 200 °C. On comparing the peroxidase-like catalytic efficiency, we found that solid Au–Ag@HNT (200 °C) maintained the same catalytic efficiency as porous Au–Ag@HNT, although solid Au–Ag@HNT (400 °C) showed lower catalytic efficiency ( Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Gold nanoshells represent a spherical layer of gold around a filled or hollow core that can either be solid or porous, [22,23] with the latter possessing notable catalytic [24] and surface-enhanced Raman scattering (SERS) activity. [25,26] To better probe the features of a BAuNS and its external gold layer, we extended the morphological characterization by close-up inspection of its edges via TEM.…”
Section: Introductionmentioning
confidence: 99%